Androgen deprivation promotes diabetic wound healing in mice through modulation of wound microbiome and immune response - Sun, Ziyang; Huang, Rizhong; Chen, Jingyi; Song, Yangyu; Sun, Zihao; Zhang, Lixiang; Shi, Huaikai; Mu, Ruoyu; Wang, Yiwei; Huang, Jinlong; Yan, Xin; Tan, Qian (Frontiers in Microbiology, 2025)
IntroductionDelayed wound healing is a major complication of diabetes, often associated with chronic inflammation and microbial dysbiosis. Although androgens are known to impair wound repair, their role in diabetic wound healing, particularly in regulating the local wound microbiome and associated immune response, remains poorly understood. In this study, we investigated whether androgen deprivation via surgical castration could enhance diabetic wound healing by modulating local microbial communities and inflammation.MethodsA full-thickness wound model was established in db/db mice. Surgical castration was used to achieve androgen deprivation. Wound closure and histology were assessed longitudinally. Blood glucose and body weight were monitored. The local immune microenvironment was profiled, focusing on pro-inflammatory factors and macrophage polarization. 16S rRNA sequencing characterized α-diversity and community composition over time. Functional prediction analyses inferred microbial metabolic potential, and machine-learning models evaluated taxa associated with healing dynamics.ResultsAndrogen deprivation significantly accelerated wound closure and improved histological outcomes without altering blood glucose or body weight. The wound microenvironment showed reduced pro-inflammatory factors and enhanced M2 macrophage polarization. 16S rRNA sequencing revealed increased microbial α-diversity and durable shifts in community composition, most prominently during early healing. Escherichia-Shigella, Rhodococcus, and Ochrobactrum were enriched, while Staphylococcus abundance decreased. Functional prediction indicated elevated microbial metabolic activity after castration. Machine-learning analysis identified Escherichia-Shigella as a key genus associated with accelerated healing.DiscussionLow androgen levels were associated with improved diabetic wound repair, potentially by attenuating local inflammation and fostering a more diverse, metabolically active microbiota. These data support a mechanistic link among androgens, wound inflammation, and the microbiome, and suggest host-directed therapeutic strategies for chronic diabetic wounds.